(untitled) (Research, Society and Development, 2023)
Introduction: The article addresses surgery as a mechanism of risk, highlighting the breach of the body’s first line of defense and the consequent increase in the likelihood of infections. The concern is heightened by the high rates of morbidity, mortality, and significant costs associated with such infections, impacting the economy and the patients’ quality of life. Methodology: The research consists of a systematic literature review, analyzing articles from the last ten years about infections at surgical sites across various surgical specialties and after hospitalization. A hypothetical/deductive method with a quantitative approach was used, consulting databases like LILACS and SCIELO. Results and Discussion: A national study identified a surgical site infection rate of 11%. Most samples indicated a rate below 10%, suggesting a reduction in these infections in Brazil. However, the possibility of underreporting of these cases emerged. It was observed that the monitoring of the occurrence of surgical site infections is limited, in many Brazilian hospitals, to the duration of hospitalization, without systematic post-discharge follow-up. Staphylococcus aureus was highlighted as the most common microorganism in surgical site infections. Conclusion: The study concludes that continuous monitoring and data dissemination on infections are vital for improving patient surgical safety. The necessity for more effective prevention and treatment strategies, including epidemiological surveillance and post-discharge follow-up, is emphasized. The research points to the importance of future interventions so that the knowledge acquired by the entire surgical team can be utilized for the benefit of patient safety.